2017
DOI: 10.11606/issn.2317-0190.v24i4a154184
|View full text |Cite
|
Sign up to set email alerts
|

Terapia de ondas de choque focal para osteoartrose de joelho: um ensaio clínico randomizado duplo-cego

Abstract: Objetivo: Avaliar eficácia da terapia de ondas de choque focal (f-ESWT) comparada ao placebo para dor e incapacidade em pacientes com osteoartrose de joelho (OA). Métodos: Ensaio clínico randomizado, duplo-cego, placebo controlado, pacientes com OA primária de joelhos realizaram exercícios (alongamentos de isquiotibiais e fortalecimento de quadríceps) e randomizados em f-ESWT ou placebo. Todos os pacientes foram submetidos a 4 sessões semanais de 7.000 pulsos, e no grupo f-ESWT a energia foi de até 0.15mJ/mm2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The protocol used in previous studies reached up to 0.44 mJ/mm 2 with high-energy machines ( 34 36 ). However, our findings demonstrated that lower doses of 0.12 mJ/mm 2 have also reduced pain and improved functioning in a large percentage of patients ( 22 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The protocol used in previous studies reached up to 0.44 mJ/mm 2 with high-energy machines ( 34 36 ). However, our findings demonstrated that lower doses of 0.12 mJ/mm 2 have also reduced pain and improved functioning in a large percentage of patients ( 22 ).…”
Section: Discussionmentioning
confidence: 59%
“…A verbal pain score was registered at the beginning of the stimulus and at the end of the shock waves train of 2,000 pulses for each segment treated. When the level zero of pain was achieved before reaching these 2,000 pulses, the application was interrupted and the number of pulses was registered ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…The mean age in the intervention and control groups ranged from 49.9 to 70 and 49.7 to 72.4 years old, respectively. The mean body mass index was reported only in 25,2936 ranging from 23.91 to 31 kg/m 2 in the intervention group and from 24.6 to 31.1 kg/m 2 in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…RCT: Randomized Clinical Trial. 0.28 mJ/mm²) for seven studies, [25][26][27][30][31][32]36 and high energy intensity (< 0.60 mJ/mm²) by a single study. 33 Four studies did not mention the energy density used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation